2006
DOI: 10.1073/pnas.0605504103
|View full text |Cite
|
Sign up to set email alerts
|

The role of hydrophobic interactions in initiation and propagation of protein folding

Abstract: Globular proteins fold by minimizing the nonpolar surface that is exposed to water, while simultaneously providing hydrogenbonding interactions for buried backbone groups, usually in the form of secondary structures such as ␣-helices, ␤-sheets, and tight turns. A primary thermodynamic driving force for the formation of globular structure is thus the sequestration of nonpolar groups, but the correlation between the parts of proteins that are observed to fold first (termed folding initiation sites) and the ''hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
219
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 284 publications
(234 citation statements)
references
References 37 publications
(48 reference statements)
14
219
0
1
Order By: Relevance
“…These results suggest that both polarity and the nonpolar neck of K156 are required for its function (Dyson et al 2006). In the human PABP-1 RRM2, the residue equivalent to K156 is involved in packing interactions between RRM1 and RRM2, which stabilize the RNAbinding trough (Deo et al 1999).…”
Section: Clustering Mutation Sensitivity Profiles Identifies Structurmentioning
confidence: 98%
“…These results suggest that both polarity and the nonpolar neck of K156 are required for its function (Dyson et al 2006). In the human PABP-1 RRM2, the residue equivalent to K156 is involved in packing interactions between RRM1 and RRM2, which stabilize the RNAbinding trough (Deo et al 1999).…”
Section: Clustering Mutation Sensitivity Profiles Identifies Structurmentioning
confidence: 98%
“…The AABUF profile of apomyoglobin provides an explanation for the observed folding pathway and for the structure of the burst phase folding intermediate. It was also shown that the AABUF profile could be changed by mutagenesis to alter the kinetic folding pathway by design (Nishimura et al 2005b;Dyson et al 2006). However, for the H64F mutant, the observed change in the structure of the folding intermediate does not seem to arise from changes in the AABUF as a result of the mutation of His to Phe but rather from stabilizing hydrophobic interactions in the compact molten globule states.…”
Section: Effect Of the His64phe Mutation On The Ph 4 Intermediatementioning
confidence: 99%
“…Considering a dimerization/binding reaction A + B ⇌ AB, the absolute binding constant is defined as 16 (2) where C i is the concentration of species i and C0 is the standard concentration in the same units as C i . The subscript "D" stands for dimerization.…”
Section: Calculation Of Absolute Binding Constantsmentioning
confidence: 99%